The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1021/ed062p575
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamically and kinetically controlled products

Abstract: Parallel irreversible and reversible reactions, thermodynamic aspects and the effect of temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
4
5
0
Order By: Relevance
“…Because of the tenfold increase in the number of cells monitored, these curves are seen to be significantly smoother than those from the single trial run shown in Figure 1. The crossing point for [B] ϭ [C] was found to occur at 492 (Ϯ21, standard deviation) iterations for the ten trials, a value fairly close to that reported for the equation-based model [6]. The maximum of the B concentration occurred at 132 Ϯ 15 iterations, and the average concentration at was 0.309 Ϯ [B] max 0.003 in this instance, a value significantly different from the 0.5 value suggested by Brown et al [6].…”
Section: Case Isupporting
confidence: 80%
See 4 more Smart Citations
“…Because of the tenfold increase in the number of cells monitored, these curves are seen to be significantly smoother than those from the single trial run shown in Figure 1. The crossing point for [B] ϭ [C] was found to occur at 492 (Ϯ21, standard deviation) iterations for the ten trials, a value fairly close to that reported for the equation-based model [6]. The maximum of the B concentration occurred at 132 Ϯ 15 iterations, and the average concentration at was 0.309 Ϯ [B] max 0.003 in this instance, a value significantly different from the 0.5 value suggested by Brown et al [6].…”
Section: Case Isupporting
confidence: 80%
“…The crossing point for [B] ϭ [C] was found to occur at 492 (Ϯ21, standard deviation) iterations for the ten trials, a value fairly close to that reported for the equation-based model [6]. The maximum of the B concentration occurred at 132 Ϯ 15 iterations, and the average concentration at was 0.309 Ϯ [B] max 0.003 in this instance, a value significantly different from the 0.5 value suggested by Brown et al [6]. Moreover, our data do not exhibit the highly peaked behavior for the concentration of species B reported in their study.…”
Section: Case Isupporting
confidence: 80%
See 3 more Smart Citations